First clinical multicenter experience with the new Pipeline Vantage flow diverter - BALTACIOĞLU, FEYYAZ (My University, 2023)
Background Flow diversion is an innovative and increasingly used technique for the treatment of intracranial aneurysms. New flow diverters (FDs) are being introduced to improve the safety and efficacy of this treatment. The aim of this study was to assess the safety, feasibility, and efficacy of the new Pipeline Vantage (PV) FD. Methods Patients with intracranial aneurysms treated with the PV at 10 international neurovascular centers were retrospectively analyzed. Patient and aneurysm characteristics, procedural parameters, complications, and the grade of occlusion were assessed. Results 60 patients with 70 aneurysms (5.0% with acute hemorrhage, 90.0% located in the anterior circulation) were included. 82 PVs were implanted in 61 treatment sessions. The PV could be successfully implanted in all treatments. Additional coiling was performed in 18.6%, and in-stent balloon angioplasty (to enhance the vessel wall apposition) in 24.6%. Periprocedural technical complications occurred in 24.6% of the treatments, were predominantly FD deployment problems, and were all asymptomatic. The overall symptomatic complication rate was 8.2% and the neurological symptomatic complication rate was 3.3%. Only one symptomatic complication was device-related (perforator artery infarctions leading to stroke). After a mean follow-up of 7.1 months, the rate of complete aneurysm occlusion was 77.9%. One patient (1.7%) died due to aneurysmal subarachnoid hemorrhage which occurred before treatment, unrelated to the procedure. Conclusions The new PV FD is safe and feasible for the treatment of intracranial aneurysms. The short-term occlusion rates are promising but need further assessment in prospective long-term follow-up studies.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Surgery Medicine Sciences; Life Sciences; Natural Sciences; NÖRO-GÖRÜNTÜLEME; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); CERRAHİ; Klinik Tıp; Klinik Tıp (MED); NEUROIMAGING; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); SURGERY; CLINICAL MEDICINE; Clinical Medicine (MED); Human-Computer Interaction; Surgery; Physical Sciences; aneurysm; flow diverter; angiography; intervention; INTRACRANIAL ANEURYSMS; EMBOLIZATION DEVICE